Response assessment in paediatric intracranial ependymoma: recommendations from the Response Assessment in Pediatric Neuro-Oncology (RAPNO) working group - Lindsay, Holly B.; Massimino, Maura; Avula, Shivaram; Stivaros, Stavros; Grundy, Richard; Metrock, Katie; Bhatia, Aashim; Fernández-Teijeiro, Ana; Chiapparini, Luisa; Bennett, Jeffrey; Wright, Karen; Hoffman, Lindsey M; et al. (The lancet. Oncology, 2022)
Response criteria for paediatric intracranial ependymoma vary historically and across different international cooperative groups. The Response Assessment in the Pediatric Neuro-Oncology (RAPNO) working group, consisting of an international panel of paediatric and adult neuro-oncologists, neuro-radiologists, radiation oncologists, and neurosurgeons, was established to address both the issues and the unique challenges in assessing the response in children with CNS tumours. We established a subcommittee to develop response assessment criteria for paediatric ependymoma. Current practice and literature were reviewed to identify major challenges in assessing the response of paediatric ependymoma to clinical trial therapy. For areas in which data were scarce or unavailable, consensus was reached through an iterative process. RAPNO response assessment recommendations include assessing disease response on the basis of changes in tumour volume, and using event-free survival as a study endpoint for patients entering clinical trials without bulky disease. Our recommendations for response assessment include the use of brain and spine MRI, cerebral spinal fluid cytology, neurological examination, and steroid use. Baseline postoperative imaging to assess for residual tumour should be obtained 24-48 h after surgery. Our consensus recommendations and response definitions should be prospectively validated in clinical trials.
Gesehen am 21.02.2023